Influence of coalification on methane diffusion dynamics in middle-high rank coals - Jiang, Jingyu; Zhang, Shuo; Longhurst, Philip J.; Zhao, Ke; Wang, Deyang (Taylor & Francis, 2025)
Understanding the effect of coalification on the diffusion of methane in middle-high rank coals (MHRC) is fundamental for optimizing the coalbed methane (CBM) drainage strategies. Safe coal mining relies critically on this approach. Hence, CH4 adsorption/desorption experiments and a new methane diffusion model were used to study methane diffusion behavior in five different metamorphic degree coals from China. The results indicate that, as the vitrinite reflectance (Ro) increase, the Langmuir volume (VL) shows a downward trend at first, then increases. Coalification especially for the third coalification jump (Ro = 1.26%) shows a turning effect on diffusion dynamics of MHRC. The desorption volume and initial diffusion coefficient (D0) both show a slight decreasing, then rapid increasing trend. The D0 of five coals jumps at Ro = 1.26%. VL increases alongside that of the micropores volume. With the decrease of the Raman parameter ID1/IG, the VL, methane desorption volume within 7200 s and D0 all increase. Results show that coalification changes the microporous structure and the macromolecular structure of the coal, which finally affects the diffusion capacity of coal. Coalification has a positive effect for the gas extraction and the development of CBM for the semianthracites.
Keywords: Coalification; molecular structure; desorption; gas diffusion; Raman parameter